2019
DOI: 10.1248/bpb.b19-00567
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Intraocular-Pressure-Lowering Therapy Targeting ATX

Abstract: Elevated intraocular pressure (IOP) is the major cause of glaucoma, which is the second leading cause of blindness. However, current glaucoma treatments cannot completely regulate IOP and progression of glaucoma. Our group recently found that autotaxin (ATX) activity in human aqueous humor (AH) was positively correlated with increased IOP in various subtypes of glaucoma. To develop new IOP-lowering treatments, we generated a novel ATX inhibitor as an ophthalmic drug by high-throughput screening, followed by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Our findings are inconsistent with aberration in the LPA-ATX pathway in the glaucomatous ON, unlike that observed in the anterior eye chamber/trabecular meshwork. 44,45,[49][50][51] Aside from the ATX-LPA pathway, there are numerous metabolic mechanisms that are responsible for the synthesis and breakdown of LPLs. We evaluated several pathways that interconnect the metabolism of LPA, LPE, and LPC ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are inconsistent with aberration in the LPA-ATX pathway in the glaucomatous ON, unlike that observed in the anterior eye chamber/trabecular meshwork. 44,45,[49][50][51] Aside from the ATX-LPA pathway, there are numerous metabolic mechanisms that are responsible for the synthesis and breakdown of LPLs. We evaluated several pathways that interconnect the metabolism of LPA, LPE, and LPC ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are inconsistent with aberration in the LPA-ATX pathway in the glaucomatous ON, unlike that observed in the anterior eye chamber/trabecular meshwork. 44 , 45 , 49 51 …”
Section: Discussionmentioning
confidence: 99%
“…As previously shown, IOP stayed within the normal range in the EAG model ( Laspas et al, 2011 ; Joachim et al, 2013 ). Other studies demonstrated that topically or intracamerally administrated ATX-inhibitors acutely decreased the IOP in healthy rabbits as well as in mice with elevated pressure due to laser peripheral iridotomy ( Iyer et al, 2012 ; Nagano et al, 2019 ). In contrast, ATX-i ( 13 ), which was administered via the oral route, did not lower IOP in both models.…”
Section: Discussionmentioning
confidence: 99%
“…Such an imbalance of ATP and ADP may cause dysregulation in IOP‐regulating purinergic signalling and pathological IOP elevation. Normalization of the imbalance by pharmacological blockade of ENPP2 successfully reduces IOP to basal levels in animal models (Nagano et al, 2019). Thus, our present finding is not just an artefact in the mouse model but is related to pathogenic mechanisms in human glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%